Soft modes in N $$ \mathcal{N} $$ = 2 SYK model - Cheng Peng; Stefan Stanojevic (Journal of High Energy Physics, 2021)
Abstract We study various properties of the soft modes in the N $$ \mathcal{N} $$ = 2 supersymmetric SYK model.